STUDI KELAYAKAN ARKEOLOGI DI KOMPLEKS MAKAM IMOGIRI, YOGYAKARTA: STUDI AWAL DALAM RANGKA PERENCANAAN PENELITIAN ARKEOLOGI - Chawari, Muhammad (BRIN, 2008)
Feasibility study and archaeological research had been arranged as the object of cultural law (UU No. 5 Tahun 1992) and government regulation (PP No. 10 Tahun 1993) about the implementation of object of cultural law (UU No. 5 Tahun 1992). However, feasibility study related to archaeological research is still rarely conducted. This paper aims to set forth the relevancy of feasibility study as a preliminary activity to reach a more comprehensive archaeological research.